SADRANAN TRADITION OF KECANDRAN SALATIGA’S SOCIETY IN ISLAMIC PERSPECTIVE - Hanif Ahmad (IAIN Bone, 2021)
The Sadranan tradition is a tradition that has existed for a long time since ancient times, especially in the Kecandran area. The results show the Sadranan is held once a year, usually in mid-November and June. All from various backgrounds follow this Sadranan tradition. This tradition is carried out after the month of Shuro. The purpose of Sadranan is; first, this tradition is gratitude to Allah SWT for pleasure, and the second is as a form of respect for ancestors. Third, strengthen a sense of solidarity between citizens. Fourth, preserving the traditional inter and indigenous cultures of the area. Some benefits felt by the community are that people feel closer to Allah SWT.